CFD and techno-economic modelling of the effect of feed spacer on reverse osmosis membrane performance - Toh, Kang Yang (2020)
Reverse osmosis (RO) processes are among the most popular solutions for brackish water and seawater desalination. One of the major issue faced in RO membrane is concentration polarisation (CP). As feed spacer geometry has major impacts on the flow and CP in the spiral wound membrane (SWM), optimizing its geometry remains an ongoing research goal. This thesis systematically investigates the effect of feed spacer geometry on RO membrane performance through computational fluid dynamics (CFD) and technoeconomic modelling. For CFD study, two different spacer designs are considered: 1) spacer with perforations and 2) spacer with different floating characteristics. The main finding from the spacer perforation is that it does not improve mass transfer for the cases simulated using conventional spacers. It was also shown that spacers with larger perforation decrease mass transfer by over 10% due to weakening of the flow velocity and suppression of vortex shedding. The simulation results also reveal that the floating ratio (Rf) is not a determining factor for permeate flux enhancement. This is because the transport mechanism is more dependent on other geometric characteristics, such as a 2 -or 3-layer design. The techno-economic modelling reveals that advanced spacers are more effective than conventional spacers in improving flux in the region close to the inlet for high-permeance membranes. This is due to the fast decrease in feed flow along the channel. This thesis found that an increase in membrane permeance (up to 10 L m−2h−1 bar−1) can reduce total processing cost of SWRO and BWRO by 7.5% and 32%, respectively regardless of spacer type used. The main finding from technoeconomic analysis is that improving spacer design is more crucial than increasing permeance at same recovery.